2022
DOI: 10.3390/pathogens11050534
|View full text |Cite
|
Sign up to set email alerts
|

Antiretroviral Drug-Resistance Mutations on the Gag Gene: Mutation Dynamics during Analytic Treatment Interruption among Individuals Experiencing Virologic Failure

Abstract: We describe drug-resistance mutation dynamics of the gag gene among individuals under antiretroviral virologic failure who underwent analytical treatment interruption (ATI). These mutations occur in and around the cleavage sites that form the particles that become the mature HIV-1 virus. The study involved a 12-week interruption in antiretroviral therapy (ART) and sequencing of the gag gene in 38 individuals experiencing virologic failure and harboring triple-class resistant HIV strains. Regions of the gag gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…However, most of these mutations did not revert to the wild type after 12 months of analytical treatment interruption (ATI). Conversely, mutations outside the gag cleavage sites, specifically R76K and Y79F, exhibited a reversion to wild type in most cases after ATI 23 .…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…However, most of these mutations did not revert to the wild type after 12 months of analytical treatment interruption (ATI). Conversely, mutations outside the gag cleavage sites, specifically R76K and Y79F, exhibited a reversion to wild type in most cases after ATI 23 .…”
Section: Discussionmentioning
confidence: 97%
“…Another study used the inverse substrate-protease analysis to determine gag mutations associated with PI resistance upon reversion to wild type after analytical antiretroviral treatment interruption among PLH experiencing failing PI treatment 23 . In this study, the Y132F mutations at the gag cleavage site were identified.…”
Section: Discussionmentioning
confidence: 99%